2006
DOI: 10.1016/s1556-0864(15)31627-0
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Prediction Rule to Estimate the Probability of Mediastinal Metastasis in Patients with Non-small Cell Lung Cancer

Abstract: We analyzed data from a randomized controlled trial of selective versus routine mediastinoscopy that was performed by the Canadian Lung Oncology Group. The study enrolled 685 patients with potentially resectable lung cancer from six centers in Canada between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Previous studies showed age as an independent predictor of N2 lymph node metastasis in NSCLC or those with T1 disease. 17,18 In our study, it was not found to be a relevant factor for nodal involvement in univariate analysis (P = 0.56), which was also observed in the study by Fuwa et al 27 According to multivariate analysis, however, age seemed to be an independent risk factor (OR 0.65, P < 0.0001), which means younger patients were more prone to having lymph node metastases. There was no statistical difference between AD and SCC in the light of the study by Yu et al 28 However, in our study, we found that patients with tumor histology of SCC were much more likely to have lymph node metastases (30.4%) compared with AD patients.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies showed age as an independent predictor of N2 lymph node metastasis in NSCLC or those with T1 disease. 17,18 In our study, it was not found to be a relevant factor for nodal involvement in univariate analysis (P = 0.56), which was also observed in the study by Fuwa et al 27 According to multivariate analysis, however, age seemed to be an independent risk factor (OR 0.65, P < 0.0001), which means younger patients were more prone to having lymph node metastases. There was no statistical difference between AD and SCC in the light of the study by Yu et al 28 However, in our study, we found that patients with tumor histology of SCC were much more likely to have lymph node metastases (30.4%) compared with AD patients.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, in view of the significant association of age with N2 lymph node metastasis in NSCLC or T1 NSCLC reported previously, it was also included into the multivariate analysis. 17,18 All variables with P ≤ 0.2 were retained in the final model. All statistical analyses were two-sided, and were carried out using SAS version 9.4 (SAS Institute, Cary, NC, USA).…”
Section: Discussionmentioning
confidence: 99%
“…A study on 503 patients with completely resected invasive T1 NSCLC revealed that tumor size independently affected nodal metastasis. 22 Shafazand and Gould 20 showed that age less than 65 years was an independent predictor of mediastinal lymph node metastasis. Younger patients with NSCLC were more likely to present with more aggressive disease and have a lower degree of suspicion of lung cancer, which might lead to delayed diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Beside information derived from LNs, characteristics of the primary tumor and clinical data of the patients are also useful in LN staging. Previous studies developed several prediction models for N2 disease in NSCLC [8,18,19]. In these models, younger age, larger tumor size, central tumor location, and adenocarcinoma were independent predictors.…”
Section: Commentmentioning
confidence: 99%